Estimating the impact of wide scale uptake of screening and medications for opioid use disorder in US prisons and jails - Macmadu, Alexandria; Goedel, William C.; Adams, Joëlla W.; Brinkley-Rubinstein, Lauren; Green, Traci C.; Clarke, Jennifer G.; Martin, Rosemarie A.; Rich, Josiah D.; Marshall, Brandon D.L. (Drug and alcohol dependence, 2020)
•Medications for opioid use disorder in prisons/jails reduced overdose post-release.•Our model predicted that treatment alone would have saved 1840 lives.•We predicted that treatment and post-release retention would have saved 4400 lives. Medications for opioid use disorder (OUD) are the most effective treatment for OUD, but uptake of these life-saving medications has been extremely limited in US prisons and jail settings, and limited data are available to guide policy decisions. The objective of this study was to estimate the impact of screening and treatment with medications for OUD in US prisons and jails on post-release opioid-related mortality. We used data from the National Center for Vital Statistics, the Bureau of Justice Statistics, and relevant literature to construct Monte Carlo simulations of a counterfactual scenario in which wide scale uptake of screening and treatment with medications for OUD occurred in US prisons and jails in 2016. Our model predicted that 1840 (95% Simulation Interval [SI]: -2757 – 4959) lives would have been saved nationally if all persons who were clinically indicated had received medications for OUD while incarcerated. The model also predicted that approximately 4400 (95% SI: 2675 – 5557) lives would have been saved nationally if all persons who were clinically indicated had received medications for OUD while incarcerated and were retained in treatment post-release. These estimates correspond to 668 (95% SI: -1008 – 1812) and 1609 (95% SI: 972 – 2037) lives saved per 10,000 persons incarcerated, respectively. Prison and jail-based programs that comprehensively screen and provide treatment with medications for OUD have the potential to produce substantial reductions in opioid-related overdose deaths in a high-risk population; however, retention on treatment post-release is a key driver of population level impact.